Visualising urban commoning: geographies of precarity, defiance and hope - Pestana Lages, Joana (2024)
In this visual essay we draw on photographs from several urban locations across Northern and Southern geographies, particularly focused on the research contexts that are explored within the papers in this Special Issue, to explore the manifold meanings, divergent practices, and variegated outcomes of urban commoning (Garcia-Lopez et al., 2021; Eidelman and Safransky, 2021; Stavrides 2016). By pursuing a visual comparative method, which included collectively selecting and discussing photographs from our research contexts, we engaged in a careful dialogue through which we made sense of the images (Rose, 2008). We deliberated on what they represent, how they relate to each other, and what aspects of the (un)commoning they illuminate. Through this process, we identified four emerging themes that we believe highlight critical aspects of the commons, while at the same time holding our different contexts in place and together: (1) Precarity, violence, demolition; (2) Defiance, hope & the city as text; (3) Advancing socio-spatial relations; (4) Commoning as Human – non-human relations. Inevitably, there are many ways to interpret and categorise these images, since each photograph has multiple meanings and illustrates various facets of the commoning processes and practice. Nonetheless, through this method, we have been able to establish links between various places and geographies, highlighting the multiplicity and overlaps of common use practices.